Correlation of P-wave Velocity with Rock Quality Designation (RQD) in Volcanic Rocks - Teuku Faisal Fathani; Ainul Fatayaatis Salaamah; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2019)
One important part of rock mass investigation is the geomechanical assessment in terms of rock mass classification systems. Rock mass classification is one of the most efficient methods in rock mechanics to provide a basic understanding of rock mass characterization. Rock mass properties can be determined by a seismic refraction survey as an indirect geophysical assessment. In this study, the P-wave velocity from seismic refraction was compared with the Rock Quality Designation (RQD) from the boreholes. The empirical correlation between the RQD and the P-wave velocity was found by using the linear regression analysis. The RQD value estimated from the P-wave velocity can beapplied for tropical environment study with geological conditions of volcanic rocks. This study helps to estimate and predict the subsurface rock quality, to reduce investigation costs, and to improve understanding of subsurface rock quality.